The kings of Clonmel - Flanagan, John (John Anthony) (New York : Philomel Books, 2010)
Halt, Will, and Horace set out for Hibernia, where a quasi-religious group, the Outsiders, is sowing confusion and sedition, and they find that secrets from Halt's past may hold the key to restoring order before the last kingdom is undermined.
Wilson's Junior High School, September 2011.
Horn Book, October 2010.
Wilson's Junior High School.
Horn Book.
6.1
5-8
Keywords: Insurgency -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Cults -- Juvenile fiction; Insurgency -- Fiction; Kings, queens, rulers, etc. -- Fiction; Cults -- Fiction; War -- Fiction; Fantasy; Insurgency -- Fiction; Kings and rulers -- Fiction; Cults -- Fiction; War stories; Fantasy fiction; Insurgency -- Fiction; Kings, queens, rulers, etc. -- Fiction; Cults -- Fiction; War -- Fiction; Fantasy; War stories; Fantasy fiction